Pengaruh Profitabilitas, Likuiditas, Kebijakan Dividen, Non Performing Loan, dan Capital Adequacy Ratio Terhadap Nilai Perusahaan Perbankan 2019–2023 - Michael Alamsyah; Dodi Ria Atmaja (MES Management Journal, 2026)
This study aims to examine the effect of profitability, liquidity, dividend policy, non-performing loans (NPL), and capital adequacy ratio (CAR) on firm value in the banking sector listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. The research sample consists of 55 observational data points taken from 11 banking sub-sector entities using purposive sampling and secondary data. The analysis in this study uses Multiple Linear Regression to examine the relationship between independent variables and firm value as the dependent variable. The results show that profitability has a positive and the most dominant effect on firm value. In addition, NPL (Non-Performing Loan) also affects company value. Interestingly, liquidity shows a negative relationship with company value, contrary to the proposed positive hypothesis. Meanwhile, dividend policy and CAR (Capital Adequacy Ratio) do not show any influence on company value. These findings are expected to provide insights for bank management and stakeholders in making strategic decisions related to risk management and investment, as well as offer valuable information for investors in assessing investment opportunities in the banking sector to achieve optimal returns.